2010
DOI: 10.1002/bdrb.20264
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and reproduction: effects of zinc deficiency on prenatal and early postnatal development

Abstract: A large body of evidence supports the concept that human pregnancy outcome is significantly influenced by the nutritional status of the mother. The consumption of "poor diets" has been associated with an increased risk for pregnancy complications, including gross structural birth defects, prematurity, low birth weight, and an increased risk for neurobehavioral and immunological abnormalities after birth. Forty-four years ago, zinc deficiency in mammals was shown to be teratogenic. Maternal zinc deficiency prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 142 publications
4
87
1
1
Order By: Relevance
“…However, the regulation of placental GLUT1 expression remains unclear [29]. In accordance with the importance of zinc for fetal development, zinc deficiency during pregnancy has reported that is associated with congenital malformations and embryonic and fetal deaths [30]. Strengths of the current study were the blinding of participants and without dropout rate.…”
Section: Discussionmentioning
confidence: 83%
“…However, the regulation of placental GLUT1 expression remains unclear [29]. In accordance with the importance of zinc for fetal development, zinc deficiency during pregnancy has reported that is associated with congenital malformations and embryonic and fetal deaths [30]. Strengths of the current study were the blinding of participants and without dropout rate.…”
Section: Discussionmentioning
confidence: 83%
“…Iron and calcium deficiencies during pregnancy contribute significantly to maternal deaths, while iron deficiency is also associated with low birth weight [3]. Furthermore, maternal zinc deficiency results in consequences ranging from fetal death to intrauterine growth retardation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc deficiency, a global problem, contributes negatively to human health and development [Maret and Sandstead 2008;Walingo 2009]. Moderate and marginal zinc deficiency, due to inadequate intake, is by far more common throughout the world than severe deficiency [Al-Timimi 2009], especially in those stages of life when requirements are increased such as infancy, childhood, and pregnancy [Fesharakinia et al 2009, Hess andKing 2009;Uriu-Adams and Keen 2010]. Zinc affects different aspects of mammalian reproduction [Dissanayake et al 2009;Björndahl and Kvist 2010].…”
Section: Introductionmentioning
confidence: 99%